Study on mechanical properties of rock and soil mass in the slip zone of shibanping landslide - Gao, Meiben; He, Binbin; Li, Wenhui; Guo, Wanjia; Bai, Shiming; Wang, Lijuan; Bian, Rui; Zhang, Liang; He, Zhihao; Lu, Feng (Frontiers in Earth Science, 2025)
The mechanical behavior of landslide rock masses and slip zone soils plays a crucial role in the initiation and evolution of landslides, particularly under prolonged rainfall conditions, where the saturation process leads to strength degradation and changes in failure mechanisms. This study focuses on the Shibanping landslide in Yunyang County, Chongqing, and systematically investigates the mechanical properties and energy evolution of the rock and soil mass in the slip zone under different saturation durations. Conventional triaxial compression tests were conducted on sandstone and argillaceous sandstone to examine their strength, elastic modulus, and failure modes under natural and saturated conditions. In situ direct shear tests were performed on slip zone soils to evaluate the degradation trend of shear strength parameters with changing water content. The results indicate that the peak strength and elastic modulus of the rock mass increase with confining pressure, while water saturation significantly weakens the rock strength, with argillaceous sandstone exhibiting greater water sensitivity and structural degradation. After saturation, the cohesion and internal friction angle of the slip zone soil decreased by 29.7% and 25.0%, respectively, leading to a pronounced reduction in shear resistance. Furthermore, energy evolution curves during the rock mass loading process reveals that energy release occurs earlier and more violently under saturated conditions, indicating a more abrupt failure process. This study can enhance the understanding of the stability evolution mechanism of rainfall-induced landslides, and provides theoretical and parameter support for disaster early warning and engineering mitigation.